Controversies in Hirschsprung surgery - Thomas O Xu; Marc A Levitt; Christina Feng (BMJ Publishing Group, 2024)
The treatment of Hirschsprung disease (HSCR) is surgical resection of aganglionic bowel and subsequent pull-through of ganglionated bowel. Despite many advances since the initial description of the disease and its surgical management more than half a century ago, there remain considerable controversies regarding the history of the surgical technique, the optimal timing of the primary and multistage pull-through, the best treatment for patients with a delayed diagnosis of HSCR, and the management of post pull-through complications such as soiling due to sphincter incompetence, the presence of a transition zone, and the prevention of enterocolitis. The following review will explore each of these controversies.